Tongues Will Cease: An Evaluation of Cessationism Based on 1 Corinthians 13:8-12 - Suwanto, Wilson W. (Riwayat: Educational Journal of History and Humanities, 2023)
The general view is that speaking in tongues will cease at Jesus' second coming as is the understanding of 1 Corinthians 13:8-12. This passage of Scripture is often used to disprove the fallacy of the Cessationist view that the gift of tongues has ceased since the Bible was written. The emphasis falls on the phrase "if the perfect arrives" which is read as referring to Jesus' return. The main argument in this paper is that verse 10 is not talking about the time of Jesus' second coming like verse 12, but rather talking about when God's perfect revelation arrives. God's perfect revelation is the Bible itself. Identifying the time frame between verses 10 and 12 is a leap of interpretation based on certain theological assumptions rather than objective facts in the text itself. Given the time frame distinction between verse 10 and verse 12, Cessationism's argument that speaking in tongues ceased after the Bible was written not only needs to be reconsidered, but also needs to be accepted as a valid and contextual interpretation of 1 Corinthians 13:812.